The Students’ Mastery in Subordinating Conjunction - Risdayanti Hasibuan; Fitriadi Lubis (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This research is discussing about students’ ability in mastering subordinating conjunction. The aim of this research was to find out the student’ ability in mastering subordinating conjunction at the fourth semester students of English Department IAIN Padangsidimpuan. This research was descriptive quantitative method that was conducted at the fourth semester IAIN Padangsidimpuan. The population of this research was fourth semester students of English department IAIN Padangsidimpuan. This research used 21 students as a sample. They were gotten by random sampling technique. The mean score of the students’ ability in mastering subordinating conjunction was 81.93. The result of this research showed the students ability in mastering subordinating conjunction was very good category.